Konsep Pendidikan dalam Kitab Ta’limul Muta’allim Karya Syekh Al-Zarnuji dan Kitab Washoya Al-Aba’ Lil-Abna’ Karya Syekh Muhammad Syakir - Moch. Mahsun; Danish Wulydavie Maulidina (Bidayatuna, 2019)
Education is very influential on students in adapting themselves and being socially sustainable to their environment. Education have concepts that must be neatly organized in carrying out educational principles with quality results and making education truly able to shape students into a smart and religious generation. The concept of education is found in the book Ta'limul Muta’allim written by Syekh Burhanuddin al-Zarnuji and the book Washoya al-aba 'lil Abna' written by sheikh Muhammad Syakir which is widely used as a guide for students at Islamic boarding schools. The two books are considered important to be compared as a reference in knowing the concept of education in the book Ta'limul Mut'allim by Sheikh Burhanuddin al-Zarnuji and the concept of education according to the book Washoya al-Aba’ lil Abna' by Syekh Muhammad Syakir. This study uses library research using documentation data collection techniques while data analysis uses descriptive qualitative techniques. Researchers found the book Ta'lim Muta'allim explained that the concept of education in this book is more likely to describe a person's moral/adab when carrying out learning and teaching activities. Meanwhile, the concept of education in the book Washoya al-Aba 'lil Abna' does not only focus on the provisions of teaching and learning, but also describes the need for a child to serve Allah and His Prophet, including describing the morals of daily life.